Transcriptome Profiling of Bovine Macrophages Infected by Mycobacterium avium spp. paratuberculosis Depicts Foam Cell and Innate Immune Tolerance Phenotypes - Ariel, Olivier; Gendron, Daniel; Dudemaine, Pier-Luc; Gévry, Nicolas; Ibeagha-Awemu, Eveline M.; Bissonnette, Nathalie (Frontiers in Immunology, 2020)
Mycobacterium avium ssp. paratuberculosis (MAP) is the causative agent of Johne’s disease (JD), also known as paratuberculosis, in ruminants. The mechanisms of JD pathogenesis are not fully understood, but it is known that MAP subverts the host immune system by using macrophages as its primary reservoir. Infection of MAP on macrophages is often studied in healthy cows or experimentally infected calves, but reports on macrophages from naturally infected cows are lacking. In our study, primary monocyte-derived macrophages (MDMs) from cows diagnosed as positive (+) or negative (−) for JD were challenged in vitro with live MAP. Analysis using next-generation RNA sequencing revealed that macrophages from JD(+) cows did not present a definite pattern of response to MAP infection. Interestingly, a considerable number of genes, up to 1,436, were differentially expressed in JD(−) macrophages. The signatures of the infection time course of 1h, 4h, 8h, and 24h revealed differential expression of ARG2, COL1A1, CCL2, CSF3, IL1A, IL6, IL10, PTGS2, PTX3, SOCS3, TNF, and TNFAIP6 among other genes, with major effects on host signaling pathways. While several immune pathways were affected by MAP, other pathways related to hepatic fibrosis/hepatic stellate cell activation, lipid homeostasis, such as LXR/RXR (liver X receptor/retinoid X receptor) activation pathways, and autoimmune diseases (rheumatoid arthritis or atherosclerosis) also reponsed to the presence of live MAP. Comparison of the profiles of the unchallenged MDMs from JD(+) versus JD(−) cows showed that 868 genes were differentially expressed suggesting these genes were already affected before monocytes differentiated into macrophages. The downregulated genes predominantly modified the general cell metabolism by downregulating amino acid synthesis and affecting cholesterol biosynthesis and other energy production pathways while introducing a pro-fibrotic pattern associated with foam cells. The upregulated genes indicated that lipid homeostasis was already supporting fat storage in uninfected JD(+) MDMs. For JD(+) MDMs, differential gene expression expounds long-term mechanisms established during disease progression of paratuberculosis. Therefore, MAP could further promote disease persistence by influencing long-term macrophage behavior by using both tolerance and fat-storage states. This report contributes to a better understanding of MAP’s controls over the immune cell response and mechanisms of MAP survival.